Effect of annealing on structure and superconducting properties in Fe(Se, Te). (June 2020) - Masi, A.; Alvani, C.; Angrisani Armenio, A.; Augieri, A.; Celentano, G.; De Marzi, G.; Fiamozzi Zignani, C.; Fabbri, F.; La Barbera, A.; Padella, F.; Rizzo, F.; Silva, E.; et al.
Abstract: In this paper, the effect of post synthesis annealing treatments on a Fe(Se, Te) polycrystalline material is evaluated and discussed. The samples have been obtained via melting route. The material has been subjected to a high-temperature annealing treatment, carried out for 45 h at 680 °C. The role of the cooling step was investigated comparing samples obtained after a controlled cooling or after quenching in liquid nitrogen. From a morpho-structural point of view, the annealing treatment improves homogeneity, with respect to pristine samples, and influences secondary phase precipitate morphology. Regarding superconducting properties, a key role of the cooling procedure is assessed: controlled cooling leads in fact to a significant improvement of high field behaviour with respect to the melted material, while quenched samples are characterized by a worsening of the superconducting properties. Despite the overall worsening, however, the quenched samples show evidence of the presence of superconducting phases characterized by a remarkably high critical temperature ( Tc > 18 K), observed for these materials only in films or under pressure.